Pelatihan Penggunaan Classpoint Sebagai Penunjang Kegiatan Pembelajaran di Kelas pada SMA Negeri 1 Parittiga - Aditya Ahmad Fauzi; Fithriawan Nugroho; Wahyu Putra; Yossa Agung Pratama; Andria Rezki; Tri Dewi Yuni Utami (Lembaga Pengembangan Kinerja Dosen, 2025)
The use of technology in education is increasingly important in creating effective and interactive learning experiences. This community service activity aims to enhance teachers' skills at SMA Negeri 1 Parittiga in utilizing ClassPoint, a Microsoft PowerPoint add-in that enables more dynamic and participatory learning. The method used includes training, demonstrations, hands-on practice, and evaluation of the technology's effectiveness. The results indicate an improvement in teachers' understanding of ClassPoint features, increased student participation in learning, and the creation of a more engaging and collaborative classroom environment. Some technical challenges, such as device limitations and internet access issues, were successfully addressed through direct assistance. This training has had a positive impact on improving teachers' digital skills and teaching effectiveness. It is expected that the implementation of this technology will contribute to the continuous improvement of learning quality.